Our priorities in international assistance (GAC, 2018)
For Global Affairs Canada, development innovation includes new or impr oved business models, policy practices, approaches, technologies, beha vioral insights or ways of delivering products and services that benef it and empower the poorest and most vulnerable people in developing co untries.